Family Approach Sebagai Strategi Pembelajaran Dalam Praktik Kebidanan Komunitas Di Akademi Kebidanan Yogyakarta - Istri Bartini; Winarsih (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Materials and modules, learning strategies and the implementation of learning in the field (practice field) correlates strongly with professional skill. One of the methods to increase participation, liveliness and skills student are learning method with the family approach in community midwifery practice. Family approach is expected to provide an effective learning experience for enhancing student competence. Currently, not all midwifery school implementing the approach as part of the activities in community midwifery practice. Yogyakarta academy of midwifery has implemented the family approach as a part of community midwifery practice.Purpose: To show the benefits and challenges of implementating active learning with the family approach in community midwifery practice.Research methods: qualitative study with focus group discussion and content analysis of student field work report. Data analysis using an explanatory building.Result and discussion: in their report, student wrote that they can find the problems in the family, think critically and creatively, practicing effective communication, approach and continuous care. In the focus group discussion, students explain how they feel happy with the famlily approach learning strategy. Its can proveide real experience for midwife in community setting. They felt this strategy would support their midwifery competencies, such as communication skills, problem solving, tend to be longlife learner. Perceived barriers were lack ot time setting to implementation family approach and ask to their lecturer.Conclussions and suggestions: family approach is fun learning activities for students and provide benefits for the improvement of midwifery skill competence in community setting. This strategy is expected to remain in community midwifery practice.Keywords: family approach, home visit, community midwifery